Gamete and Embryo-fetal Origins of Adult Diseases - Huang, He-Feng.; Sheng, Jian-Zhong.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
The book Gamete and Embryo-fetal Origins of Adult Diseases introduces various diseases resulting from the abnormal gametogenesis and embryo development, which manifests as growth retardation, birth defects, or increased susceptibility to chronic metabolic diseases such as diabetes, cardiovascular disease and cancer in childhood and adult life, even fertility disorders and the risk of transgenerational transmission. Six common kinds of these diseases are discussed in separate chapters. The authors explore the connections between these diseases and epigenetic reprogramming, rapid cell differentiation and organ formation and environmental influences, including assisted reproductive technology and adverse intrauterine environments. With a summary of findings on the causes and progression of adult diseases at the phase of gametogenesis and embryo development, this book provides insights into the pathogenesis of disease and aids in the treatment and prevention of disease, meeting the requirement for improving the quality of the newborn population, and effectively preventing and curing major diseases at an early stage. This book offers new perspectives and will be an enlightening resource for obstetricians, paediatricians, epidemiologists, endocrinologists and sanitarians. Editor He-Feng Huang, M.D., is Professor and President of Women$1 (Bs Hospital, School of Medicine, Zhejiang University, China. Editor Jian-Zhong Sheng, Ph.D., is Professor at the Department of Pathology & Pathophysiology, School of Medicine, Zhejiang University, China.s
Physiology of gametogenesis -- Physiology of embryo development -- Diabetes originated from embryo-fetal development -- Cardiovascular disease originated from embryo-fetal development -- Tumor originated from embryo-fetal development -- Obesity originated from embryo-fetal development -- Infertility originated from embryo-fetal development -- Mental health originated from embryo-fetal development -- Assisted reproductive technology (ART) and embryo-fetal origin of diseases -- Adverse intrauterine environment and embryo-fetal origin of diseases.
Keywords: Medicine; Human genetics; Pediatrics; Reproductive Medicine; Medicine & Public Health; Reproductive Medicine; Pediatrics; Human Genetics